2010
DOI: 10.1163/156853010x524361
|View full text |Cite
|
Sign up to set email alerts
|

Critique of a Critique: Do Zoos and Aquariums Promote Attitude Change in Visitors?

Abstract: Marino et al. (2010) recently published a critique of a three-year National Science Foundation-funded investigation of the impact of zoo and aquarium visits on the public's understanding of animals and their attitudes toward conservation (Falk, Heimlich, & Bronnenkant, 2008;Falk, Reinhard, Vernon, Bronnenkant, Deans, & Heimlich, 2007;Heimlich, Bronnenkant, Witgert, & Falk, 2004). This critique of that critique will show that Marino et al. seriously misrepresent both the intent of the research and the methods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 13 publications
3
45
0
2
Order By: Relevance
“…Dawson and Jensen [] are equally critical, stating that “Moreover, Falk et al did not develop valid and convincing evidence of ‘what visitors did in the institution' or of ‘long‐term meaning' (p.10); as such, this headline conclusion from the MIRP study is questionable at best” (p.136). Falk et al [] provide a defense of their research, claiming that Marino et al misrepresented the intent of the research and the methods used. Falk et al [] conclude by criticizing Marino et al's more general assertion regarding the universal lack of evidence regarding zoo visitor impact, stating that they “seriously question the authors' [Marino et al] use of this single, flawed critique, however, as the basis for their sweeping conclusion that there is no evidence that zoos and aquariums impact their visitors” (p.418).…”
Section: Educational Goals Of Member Zoosmentioning
confidence: 99%
See 1 more Smart Citation
“…Dawson and Jensen [] are equally critical, stating that “Moreover, Falk et al did not develop valid and convincing evidence of ‘what visitors did in the institution' or of ‘long‐term meaning' (p.10); as such, this headline conclusion from the MIRP study is questionable at best” (p.136). Falk et al [] provide a defense of their research, claiming that Marino et al misrepresented the intent of the research and the methods used. Falk et al [] conclude by criticizing Marino et al's more general assertion regarding the universal lack of evidence regarding zoo visitor impact, stating that they “seriously question the authors' [Marino et al] use of this single, flawed critique, however, as the basis for their sweeping conclusion that there is no evidence that zoos and aquariums impact their visitors” (p.418).…”
Section: Educational Goals Of Member Zoosmentioning
confidence: 99%
“…Falk et al [] provide a defense of their research, claiming that Marino et al misrepresented the intent of the research and the methods used. Falk et al [] conclude by criticizing Marino et al's more general assertion regarding the universal lack of evidence regarding zoo visitor impact, stating that they “seriously question the authors' [Marino et al] use of this single, flawed critique, however, as the basis for their sweeping conclusion that there is no evidence that zoos and aquariums impact their visitors” (p.418). However, it is likely that some damage will have been done to the credibility of the original work (rightly or wrongly) simply because the work has been being targeted by published criticism.…”
Section: Educational Goals Of Member Zoosmentioning
confidence: 99%
“…zoos and aquariums each year, and research suggests that they come away better informed, feeling more connected to nature, and seeing themselves as part of the solution in conservation (Falk et al, 2007). …”
Section: Effective Outreach and Educationmentioning
confidence: 99%
“…They showed that zoos in general give people a chance to observe wildlife that they may otherwise never see (Carr and Cohen, 2011;Randler et al, 2007). Visitors believe zoos play an important role in conservation, animal care and education, and that they experience a stronger connection to nature as a result of their visit Carr and Cohen, 2011;Falk et al, 2007). During a three year period, Falk et al (2007) studied more than 5 500 visitors in 12 zoos and aquariums using various quantitative and qualitative methods, like questionnaires, interviews and tracking studies.…”
Section: Introductionmentioning
confidence: 99%
“…Visitors believe zoos play an important role in conservation, animal care and education, and that they experience a stronger connection to nature as a result of their visit Carr and Cohen, 2011;Falk et al, 2007). During a three year period, Falk et al (2007) studied more than 5 500 visitors in 12 zoos and aquariums using various quantitative and qualitative methods, like questionnaires, interviews and tracking studies. They found that zoos and aquariums can enhance visitors' knowledge and understandings of wildlife and conservation, as well as their con-nection to nature, prompting individuals to reconsider their role in environmental problems and conservation actions.…”
Section: Introductionmentioning
confidence: 99%